Phosphorylation of 9-(2-phosphonomethoxyethyl)adenine and 9-(S)-(3-hydroxy-2-phosphonomethoxypropyl)adenine by AMP(dAMP) kinase from L1210 cells - Merta, A; Votruba, I; Jindrich, J; Holý, A; Cihlár, T; Rosenberg, I; Otmar, M; Herve, T Y (Biochemical pharmacology, 1992)
Acyclic nucleotide analogues 9-(2-phosphonomethoxyethyl)adenine (PMEA) and 9-(S)-(3-hydroxy-2-phosphonomethoxypropyl)adenine ((S)-HPMPA) which display potent antiviral activity are transformed in the cells to their mono- and disphosphoryl derivatives. We purified from mouse L1210 cells the enzyme that in two steps phosphorylates PMEA and (S)-HPMPA to their diphosphoryl derivatives and found that it co-purifies with AMP(dAMP) kinase activity; the best substrates of this enzyme were AMP, ADP and dAMP. Other nucleoside 5'-triphosphates or creatine phosphate could not be substituted for ATP as a phosphate donor. Our results also indicated that at least one other enzyme (creatine kinase) is capable of transforming the monophosphoryl derivatives of the studied compounds to their respective diphosphates.
Keywords: Creatine Kinase; molekulová hmotnost; Adenylate Kinase; Organophosphonates; Adenine; Isoelectric Point; Molecular Weight; organofosforové sloučeniny; adenin; izoelektrický bod; Leukemia L1210; Time Factors; substrátová specifita; leukemie L1210; Animals; Organophosphorus Compounds; Substrate Specificity; organofosfonáty; zvířata; časové faktory; nádorové buňky kultivované; myši; kreatinkinasa; Tumor Cells, Cultured; Mice; adenylátkinasa